2022
DOI: 10.1002/jmv.27694
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged fecal shedding of SARS‐CoV‐2 in a young immunocompetent COVID‐19 patient: A case report and literature overview

Abstract: Clinicians are facing several challenges in tackling coronavirus disease 2019 (COVID‐19); one issue is prolonged detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA. Here, we describe a case of SARS‐CoV‐2 infection in a young immunocompetent patient with a virological course lasting for 71 days. Following antiviral treatment, but no additional glucocorticoid or interferon therapy, the patient recovered from COVID‐19 pneumonia (moderate). Detection of viral RNA via throat swabs showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has been previously suggested that sputum PCR testing can provide clinically significant indications for persistent viral shedding ( 12 ). An increasing number of studies suggest that persistent viral shedding occurs in the lower part of the airways ( 13 ) and gastrointestinal tract ( 14 ), even after nasopharyngeal swabs demonstrate negative results. In this report, we propose the application of a PCR test to sputum samples obtained during airway intubation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that sputum PCR testing can provide clinically significant indications for persistent viral shedding ( 12 ). An increasing number of studies suggest that persistent viral shedding occurs in the lower part of the airways ( 13 ) and gastrointestinal tract ( 14 ), even after nasopharyngeal swabs demonstrate negative results. In this report, we propose the application of a PCR test to sputum samples obtained during airway intubation.…”
Section: Discussionmentioning
confidence: 99%
“…According to certain clinical trials, SARS-CoV-2 RNA continued to be excreted in the faeces for up to seven weeks after the commencement of the first symptom. Xiao discovered that viral RNA reappearance in the sample stool as well as lasted for another 27 days, indicating that SARS-CoV-2 has a long-term faecal shedding capability, even in patients with strong immune-competent capacities ( Xiao et al 2022 ). Further research revealed that even in cases when the throat swab test came back negative, viral RNA could be found in 81.8% of individuals' faeces ( Ling et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the rapid clearance of SARS-CoV-2 from the nasopharyngeal after the first few weeks of infection, the persistence of the virus in the GI tract and stool samples may provide an alternative means to study viral variants genetically identified post hoc in non-infectious, post-acute individuals. A recent study demonstrated the feasibility of viral detection in stool samples of patients for as many as 77 days after infection [19], though more normally stool samples have returned positive results up to 33 days after a negative nasopharyngeal test [20]. However, whether the full viral genome remains intact in stool sample and amenable to sequencing has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%